The Role of Chinese EMI Teachers’ Clarity and Credibility in Fostering Students’ Academic Engagement and Willingness to Attend Classes - Zheng, Jin (Frontiers in Psychology, 2021)
Given the fact that students’ absence and disengagement are among the major challenges that teachers experience in educational contexts, investigating factors contributing to students’ academic engagement and willingness to attend classes is of high importance. These challenges are more common in English as a medium of instruction (EMI) classes wherein students are usually not skilled enough to participate in academic tasks and activities. Accordingly, the present study probed into the role of Chinese EMI teachers’ clarity and credibility in fostering students’ academic engagement and willingness to attend classes. In doing so, the E-version of Teacher Clarity Short Inventory (TCSI), Source Credibility Scale (SCS), Utrecht Work Engagement Scale for Students (UWES-S), and Willingness to Attend Classes Questionnaire (WTAC) were virtually distributed among 832 Chinese college students. Performing correlational analyses, strong associations were found between teachers’ clarity and credibility and students’ academic engagement and willingness to attend classes. To assess the power of Chinese EMI teachers’ clarity and credibility in predicting students’ academic engagement and willingness to attend classes, structural equation modeling (SEM) was employed. The results of SEM analysis illuminated that both teacher clarity and credibility are strong predictors of students’ academic engagement and willingness to attend classes. The implications of the findings are also discussed.